Non-Woven Fabrics 2016
DOI: 10.5772/61511
|View full text |Cite
|
Sign up to set email alerts
|

Damage Prediction in Woven and Non-woven Fabric Composites

Abstract: This chapter presents a step-by-step review on different damage prediction approaches for woven and non-woven fabric composites. First, the characteristics of woven and nonwoven fabrics are distinguished one from another, suggesting more complex analyses required for non-woven fabrics. Then, the subsequent subsections are geared toward a comparison of different approaches utilized in predicting the mechanical behavior and damage mechanisms of these composites at various material scales including micro, meso, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Among different types of composite reinforcements, woven fabrics have gradually become a material of choice by designers, owing to their high formability, stiffer out-of-plane behavior, and superior delamination resistance compared to unidirectional composite reinforcements [1,2]. Considering this premise, fundamental knowledge and understanding of woven fabrics' forming processes and deformation mechanisms are essential for taking full advantage of their performance in high-volume productions [3].…”
Section: Introductionmentioning
confidence: 98%
“…Among different types of composite reinforcements, woven fabrics have gradually become a material of choice by designers, owing to their high formability, stiffer out-of-plane behavior, and superior delamination resistance compared to unidirectional composite reinforcements [1,2]. Considering this premise, fundamental knowledge and understanding of woven fabrics' forming processes and deformation mechanisms are essential for taking full advantage of their performance in high-volume productions [3].…”
Section: Introductionmentioning
confidence: 98%
“…A UD laminate can be considered as such, while a laminate reinforced with symmetric fabrics cannot. Application of the Hashin type failure criteria to predict the damage onset in fabric reinforced laminates was questioned in [ 34 , 38 , 39 ]. Furthermore, it was shown that the application of much simpler maximum stress criterion (which is similar to the maximum strain criterion), yielded better results.…”
Section: Methodsmentioning
confidence: 99%
“…The sensor is manufactured as a combination between 3 materials (Figure 2). A honeycomb mesh is placed between a highly conductive bottom fabric material from Less EFM [31] and a highresistance piezoresistive fabric material from Eeonyx Corp [32]. By placing the honeycomb mesh, we ensure the top and bottom layer are in contact only when a input touch is applied over the sensor.…”
Section: Skin Fabricationmentioning
confidence: 99%